Early detection and treatment of lame cows - Schulz, T.; Gundelach, Y.; Feldmann, M.; Hoedemaker, M. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2016)
Objective: The aim of this study was to investigate the impact of specific hoof lesions on the locomotion score (LS) as well as the effect of early detection and treatment on duration and prevalence of lesion-specific lameness. Material and methods: In a dairy herd in Lower Saxony, Germany, with 144 lactating cows, claw trimming was performed by a professional claw trimmer at the beginning and the end of a 41-week trial period. Weekly a veterinarian assessed the LS according to Sprecher et al. (1997) in 99 cows. The front and hind claws of cows with an LS > 1 were examined and treated within 5 days. For individual diagnoses, the duration of lameness was calculated as the number of weeks from first treatment until recovery (LS = 1).Results: In total, 580 examinations and treatments were performed on 94 cows. There were 189 new lameness cases with a total of 290 diagnoses. At the first treatment, 81.0% of the cows displayed an LS of 2. Cows with digital dermatitis (DD), heel horn erosion and white line disease (WLD) more often had an LS > 2 compared to cows with Rusterholz’ sole ulcer, interdigital hyperplasia or inadequate claw length/posture (p < 0.05). Cows with only one affected leg, more often had an LS > 2 than cows with several affected legs (p < 0.1). Lameness caused by WLD and arthritis/ periarthritis remained for the longest time period. The prevalence of sole haemorrhages and/or double soles, WLD, interdigital dermatitis and interdigital hyperplasia decreased significantly during the test period. Prevalence of sole ulcer (sole ulcer and Rusterholz’ sole ulcer) and DD remained unaffected. Conclusion and clinical relevance: Locomotion score was affected by the type of claw/limb disorder and the number of diseased limbs. Regular locomotion scoring and continuous treatment of cows with an LS > 1 is associated with a decrease in the prevalence of several claw lesions. Therefore, prevalence of severe claw lesions like WLD, which was associated with a long duration of lameness, can be reduced. In con trast, for decreasing prevalence of digital dermatitis more than weekly treatment of every cow with LS > 1 is required. Preventive measures like footbaths or improved hygiene should accompany the individual animal treatment.
Keywords: Locomotion disorder; locomotion score; herd health management